Long-term effects of climate change on grassland soil systems: a reciprocal transplant approach - Rostkowski, Steven Charles Jr. (Kansas State University, 2011)
Climate change predictions for the Great Plains region of North America include increased temperatures, changes to annual precipitation, and reduced growing season precipitation, which will likely alter grassland soil systems. To date, few studies have examined belowground community responses to predicted climate change scenarios, with fewer assessing long-term changes. My research focused on the impacts of long-term changes in precipitation and associated soil water content on belowground grassland systems (belowground plant biomass, soil carbon (C) and nitrogen (N) pools, microbial biomass C and N, and invertebrate communities) using recently collected samples from a long-term (16-yr) reciprocal core transplant between Konza Prairie Biological Station (MAP = 850 mm) and Kansas State Agricultural Research Center at Hays (MAP = 580 mm), with the Hays site having a long-term average annual precipitation amount that is ~30% less than the Konza site. Results from the experiment indicate that either increases or decreases in annual precipitation can have profound effects on belowground grassland systems. Belowground plant biomass, microbial biomass, and potential C mineralization rates were greater at the wetter Konza site regardless of soil origin. Total C stored in soils incubated at Konza was significantly greater as well, likely due to greater root inputs. The effects of precipitation were most apparent in the surface soil layers (0-20 cm), while soil origin impacted soil properties to a greater extent with increasing depth. This contrasted with results for the soil mesofauna, where total microarthropods responded negatively and nematodes responded positively to increased annual precipitation. Results of this study indicate important changes in soil C and N pools, belowground plant biomass, and soil mesofauna within grassland systems subject to changing precipitation regimes, and suggest more mesic prairie systems are more sensitive to changes in soil water availability than those in more arid grassland systems.
Keywords: Nematodes; Microarthropods; Roots; Soil Carbon; Climate Change; Grasslands; Biology, Ecology (0329)